EFFORTS TO OVERCOME THE LACK OF INTEREST IN READING REFERENCE BOOK OF COURSES IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 (A STUDY OF MASTER STUDENTS IN ISLAMIC EDUCATION CLASS OF 2018) - Muhtadin Muhtadin (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
The title of this research is efforts to overcome lack of interest in reading reference book of courses in the industrial revolution 4.0 case study on student masters PAI class 2018. This research aims to know efforts by students for overcoming the lack of interest in reading of main reference book at an educational institution that is University. In addition, this study also aims to know the factors that cause lack of interest in reading so that we know how to overcome it. This research was conducted using descriptive qualitative research methods. Data were obtained by observing in advance during the learning process in class, then followed by some interviews which is considered to have understanding about the issues that will be investigated, regarding the efforts made to overcome the lack of interest in reading Student of Islamic religious education studies Masters Program FITK class 2018 towards the Lecture Reference Book in the Industrial Revolution Era 4.0. The results showed that the reasons of low interest in reading are they don't have reference book, the books are too thick, and lack of awareness of the importance of reading reference books. The efforts that students have to do are buying a lot of books, increasing and straightening the intention to read, turning on self awareness that reading reference books as an effort to quickly graduate.